Phase I dose-escalation study of F50067, a humanized anti-CXCR4 monoclonal antibody alone and in combination with lenalidomide and low-dose dexamethasone, in relapsed or refractory multiple myeloma - Fouquet, Guillemette (Oncotarget, 2018)
PURPOSE: Multiple myeloma (MM) remains an incurable disease as tumor cells ultimately resist to all available drugs. Homing of tumor cells to the bone marrow microenvironment, involving especially the CXCR4/SDF-1 axis, allows them to survive, proliferate and resist to therapy. F50067, a humanized anti-CXCR4 IgG1 antibody, has promising preclinical activity in MM. We present a phase I multicenter escalation study in relapsed/refractory MM (RRMM) to determine the maximum tolerated dose (MTD) for F50067 alone and in combination with lenalidomide and low dose dexamethasone (Len-Dex). EXPERIMENTAL DESIGN: 14 end-stage RRMM patients received F50067 single agent (n = 10) or in combination with Len-Dex (n = 4). RESULTS: One dose-limiting toxicity was observed, a grade 4 neutropenia lasting more than 7 days in combination arm. MTD could not be established. Thrombocytopenia was observed in 100% and neutropenia in 92.9% of patients with no cases of febrile neutropenia and no severe bleeding or hematoma. Non-hematological adverse events were of mild to moderate severity. Nine patients (6 in single arm and 3 in combination arm) were evaluable for response, with 66.7% overall response rate (≥PR) in combination arm, and 33.3% of disease control (≥SD) in single agent arm. At the time of study termination, 55.6% had progressed. CONCLUSION: This study suggests that egression of tumor cells to the blood stream can represent a novel therapeutic strategy for MM. However, because of significant hematological toxicity, this study had to be discontinued. Further studies are needed to validate the feasibility of this approach in clinical practice.